Solid-state battery and preparation method thereof
By nano-modified sulfide electrolyte in the positive electrode active material layer of solid-state lithium battery, the problems of reduced energy density and poor circulation performance in the prior art are solved, and a solid-state battery with high energy density and long cycle life is realized.
Patent Information
- Application Number
- CN202411828316.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The existing solid-state lithium batteries add a large amount of sulfide electrolyte to the positive electrode active material layer to improve the conductivity, resulting in a decrease in energy density, and large-particle electrolytes are susceptible to stress, resulting in particle powdering and rupture, affecting the battery circulation performance.
By nano-transforming the modified sulfide electrolyte in the positive electrode active material layer, a tightly distributed ion transport network and a stable electrode/electrolyte interface are formed, reducing the amount of sulfide electrolyte, while increasing its structural strength and avoiding cracking and powdering during the charge and discharge cycle.
The addition of less sulfide electrolyte to the positive electrode active material layer can still ensure the good conductivity cycling performance of the battery, improve the energy density and cycle life of the battery, and enhance the storage performance of the battery.
Smart Images

Figure CN119627196A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a solid-state battery and a preparation method thereof. Background Art
[0002] All-solid-state lithium batteries are potential candidates for large-scale energy storage applications such as electric vehicles and smart grids. Solid-state electrolytes have excellent electrochemical and thermal stability, making them suitable for lithium-ion transport at high voltages and / or high temperatures.
[0003] Sulfide solid electrolytes have high electrical conductivity (10 -2 ~10 -4 S / cm 2 ) and good mechanical properties and are widely used in the manufacture of all-solid-state lithium batteries. Generally, all-solid-state lithium batteries based on sulfide solid electrolytes can only be manufactured by cold pressing, and solid electrolytes need to be added to the positive active material layer of the battery to improve the ion and electron conductivity of the active material.
[0004] Currently, due to the large size of solid electrolyte particles added to the positive electrode active material layer, the positive electrode active material layer often needs to add 30-50wt% of solid electrolyte to ensure that it has a good ion transmission channel and low interface electrode / electrolyte resistance. However, adding such a large amount of solid electrolyte to the positive electrode active material layer will greatly reduce the energy density of the battery, and the electrolyte particles with larger particle size are easily affected by the internal stress and strain of the battery, resulting in particle pulverization and rupture, thereby increasing the risk of lithium dendrites penetrating the electrolyte layer and causing the battery cycle performance to further decline.
[0005] Therefore, it is necessary to design a solid-state battery and a preparation method thereof to solve the above problems. Summary of the invention
[0006] In view of the above shortcomings of the prior art, the present invention provides a solid-state battery and a preparation method thereof, which are used to improve the technical problem that the positive electrode active material layer of the existing solid-state battery with the addition of sulfide electrolyte cannot take into account both energy density and conductivity.
[0007] To achieve the above-mentioned object and other related objects, the present invention provides a solid-state battery, which includes a positive electrode plate, the positive electrode plate includes a positive electrode active material layer, the positive electrode active material layer includes a sulfide electrolyte, and the average particle size D50 of the sulfide electrolyte satisfies 50nm≤D50<1μm; wherein the sulfide electrolyte includes Li a P 1-b M b S c O d X eand Li f P 1-g E g S w O y Q z One or more of them, 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2, 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + y < 6, 0 < z < 2, M includes at least one of Al, Ga, In, Ti, Sc, As, Sb, Bi, As, V, Nb, X includes at least one of Cl, Br, I, E includes at least one of Mg, Ca, Sr, Ba, Zn, Cr, Sn, Pb, and Q includes at least one of Cl, Br, I.
[0008] In an example of the present invention, in the sulfide electrolyte, 0 < b ≤ 0.1, and M includes at least one of Sb, In, and Bi; and / or, 0.01 ≤ g ≤ 0.1, and E includes at least Mg or Ca.
[0009] In an example of the present invention, in the sulfide electrolyte, X includes at least Cl, and Q includes at least Cl.
[0010] In an example of the present invention, the average particle size D50 of the sulfide electrolyte is 50 nm to 500 nm.
[0011] In an example of the present invention, the positive electrode active material layer includes a positive electrode active material, the mass content of the positive electrode active material in the positive electrode active material layer is 50% to 97%, and the mass content of the sulfide electrolyte in the positive electrode active material layer is 1% to 50%.
[0012] The present invention also provides a preparation method of the solid-state battery according to any one of the above examples. The preparation method includes: providing a positive electrode plate, a solid electrolyte membrane, and a negative electrode plate; assembling the positive electrode plate, the solid electrolyte membrane, and the negative electrode plate into an electric core, and encapsulating the electric core to obtain a solid-state battery;
[0013] Among them, the preparation method of the positive electrode plate includes:
[0014] Preparing a sulfide electrolyte; adding a positive electrode raw material containing a positive electrode active material, a positive electrode conductive agent, and the sulfide electrolyte and a dispersant to a solvent to obtain a mixed solution; the solvent includes a proton solvent and a non-proton solvent, and the mass ratio of the proton solvent to the non-proton solvent is 1:(1 - 10); removing the solvent in the mixed solution to obtain a composite positive electrode raw material; mixing a positive electrode binder with the composite positive electrode raw material to prepare a positive electrode coating, and coating the positive electrode coating on a positive electrode current collector to obtain a positive electrode plate.
[0015] In an example of the present invention, the mass ratio of the composite cathode material to the solvent is 1:(1 - 20).
[0016] In an example of the present invention, the protonic solvent includes at least one of ethanol and methanol, and the aprotic solvent includes at least one of toluene, xylene, benzene, acetonitrile, ether, and carbon tetrachloride.
[0017] In an example of the present invention, the dispersant includes at least one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, cetyltrimethylammonium sulfonate, sodium dodecyl sulfate, sodium dodecylbenzenesulfonate, sodium octylsulfonate, polyoxyethylene octyl ether, polysorbate, polyoxyethylene stearyl ether, sodium cocoate, sodium palmitate, sodium oleate, sodium dodecylsulfonate, and sodium polyacrylate; the mass content of the dispersant relative to the cathode material is 0.01% - 0.5%.
[0018] In an example of the present invention, the sulfide electrolyte includes Li a P 1-b M b S c O d X e and Li f P 1-g E g S w O y Q z one or more of them, 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + y < 6, 0 < z < 2, M includes at least one of Al, Ga, In, Ti, Sc, As, Sb, Bi, As, V, Nb, X includes at least one of Cl, Br, I, E includes at least one of Mg, Ca, Sr, Ba, Zn, Cr, Sn, Pb, and Q includes at least one of Cl, Br, I;
[0019] Among them, the preparation method of Li a P 1-b M b S c O d X e in the sulfide electrolyte includes: mixing a lithium source, a phosphorus source, an M source, a sulfur source, an oxygen source, and an X source according to a preset stoichiometric ratio and sintering to obtain Li a P 1-b M b S c O d X e ; and / or, Li f P 1-g E g Sw O y Q z The preparation method comprises: mixing and sintering a lithium source, a phosphorus source, an E source, a sulfur source, an oxygen source, and a Q source according to a preset stoichiometric ratio to obtain Li f P 1-g E g S w O y Q z .
[0020] The present invention provides a solid-state battery, which nanosizes a modified sulfide electrolyte doped in a positive electrode active material layer, thereby forming a tightly distributed ion transport network and a stable electrode / electrolyte interface in the positive electrode active material layer, so that a small amount of sulfide electrolyte added to the positive electrode active material layer can enable the battery to perform a good conductive cycle, thereby improving the energy density and cycle life of the battery; at the same time, the nanosized sulfide electrolyte in the positive electrode active material layer has a higher structural strength, which can avoid cracking and pulverization during the charge and discharge cycle, further improving the storage and cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other embodiments can be obtained based on these drawings without paying creative work.
[0022] Figure 1 Schematic diagram of a process for preparing a positive electrode sheet in one embodiment of the present invention;
[0023] Figure 2 This is the 1C / 1C cycle test curve of the lithium ion battery in Example 3 of the present invention. DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] In the present invention, it should be noted that the terms “first” and “second” are only used for description and distinction purposes and cannot be understood as indicating or implying relative importance.
[0026] In the present invention, proton solution refers to a solution containing protons (i.e., hydrogen ions, H + ) solution. Such solutions are usually acidic because protons are the main components of acidic substances. Protonic solutions can be produced by the ionization of acids or other chemical reactions.
[0027] In the present invention, an aprotic solution refers to a solution that does not contain protons. Such a solution may be neutral, alkaline, or other in nature. The main components of an aprotic solution may be anions (such as hydroxide ions, OH - ) or other compounds.
[0028] On the one hand, the present invention provides a solid-state battery, the positive electrode active material layer of the solid-state battery is nano-sized by doping and modifying the sulfide electrolyte to form a tightly distributed ion transmission path and a stable electrode / electrolyte interface between the positive electrode active materials in the positive electrode active material layer, so that a small amount of sulfide electrolyte is added to the positive electrode active material layer to enable the battery to perform a good conductive cycle, thereby improving the energy density and cycle life of the battery; at the same time, the nano-sized sulfide electrolyte in the positive electrode active material layer has a higher structural strength, which can avoid cracking and pulverization during the charge and discharge cycle, further improving the storage and cycle life of the battery.
[0029] The above-mentioned solid-state battery is a solid-state lithium-ion secondary battery, which includes a positive electrode plate, a negative electrode plate and a solid electrolyte membrane. The solid electrolyte membrane is arranged between the positive electrode plate and the negative electrode plate to isolate the positive electrode plate and the negative electrode plate, and serves as a lithium ion conductor between the positive electrode plate and the negative electrode plate.
[0030] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer coated on at least one side of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material, a positive electrode binder, a positive electrode conductor and a sulfide electrolyte.
[0031] The average particle size D50 of the sulfide electrolyte satisfies 50 nm ≤ D50 < 1 μm. For example, the average particle size D50 of the sulfide electrolyte can be 50 nm, 80 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, or 900 nm. Optionally, in some embodiments, the average particle size D50 of the sulfide electrolyte is 50 nm to 500 nm, for example, it can be 50 nm, 80 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, or 500 nm. The nano-sized sulfide electrolyte can be evenly distributed in the positive electrode active material layer, and increase the contact area between itself and the positive electrode active material in the positive electrode active material layer, forming a good ion transport network and a low electrode / electrolyte interface resistance in the positive electrode active material layer. It realizes that a good conductive effect can be achieved by adding less sulfide electrolyte in the positive electrode active material layer, effectively increasing the proportion of the positive electrode active material in the positive electrode and improving the energy density and cycle life of the solid-state battery. At the same time, the nano-sized sulfide electrolyte has better mechanical strength and can better withstand the strain impact caused by stress in the positive electrode active material layer, thereby reducing the risk of pulverization and cracking of the sulfide electrolyte particles and further improving the cycle life of the solid-state battery. It should be noted that the average particle size D50 refers to the particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 50%, and is also called the median diameter or median particle size. The average particle size D50 of the sulfide electrolyte can be obtained by dry testing with a HELOS-RODOS type dry laser particle size analyzer.
[0032] The sulfide electrolyte is selected from the compound of formula I Li a P 1-b M b S c O d X e and the compound of formula II Li f P 1-g E g S w O y Q z or more than one of them, wherein, 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2, 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + y < 6, 0 < z < 2, M includes at least one of Al, Ga, In, Ti, Sc, As, Sb, Bi, As, V, Nb, X includes at least one of Cl, Br, I, E includes at least one of Mg, Ca, Sr, Ba, Zn, Cr, Sn, Pb, and Q includes at least one of Cl, Br, I.
[0033] In the compound of formula I, M and X represent doping elements, and M and X elements can be any one or more combinations of the above-listed elements. For example, M element can be Al, Ga, In, Ti, Sc, As, Sb, Bi, As, V or Nb, or can be co-doped with Sb and In, or co-doped with Sb and Ti, or co-doped with Sb and Bi, or co-doped with In and Bi, or co-doped with Ti and Nb, or co-doped with Sb, Nb and V, or co-doped with Sb, In and Bi, etc.; X element can be Cl, Br or I, or can be co-doped with Cl and Br, or co-doped with Cl and I, or co-doped with Br and I, or co-doped with Cl, Br and I. Wherein, b represents the doping amount of M element, for example, b can be 0.01, 0.05, 0.1, 0.2, 0.5 or 0.8, etc.; e represents the doping amount of X element, for example, e can be 1.1, 1.3, 1.5, 1.7 or 1.9.
[0034] In the compound of formula II, E and Q represent doping elements, and the E and Q elements can be any one or more combinations of the above-listed elements. For example, the E element can be Mg, Ca, Sr, Ba, Zn, Cr, Sn or Pb, or can be co-doped with Mg and Ca, or co-doped with Mg and Zn, or co-doped with Mg and Sn, or co-doped with Ca and Ba, or co-doped with Zn and Cr, or co-doped with Mg, Ca and Sn, or co-doped with Mg, Ca and Zn, etc.; the Q element can be Cl, Br or I, or can be co-doped with Cl and Br, or co-doped with Cl and I, or co-doped with Br and I, or co-doped with Cl, Br and I. Wherein, g represents the doping amount of the E element, for example, g can be 0.01, 0.05, 0.1, 0.2, 0.5 or 0.8, etc.; z represents the doping amount of the Q element, for example, z can be 1.1, 1.3, 1.5, 1.7 or 1.9.
[0035] Compared with undoped sulfide electrolytes, sulfide electrolytes doped with metal elements and halogen elements have relatively stable chemical properties and higher ionic conductivity, and can form a stable electrode / electrolyte interface in the positive electrode active material layer, thereby reducing the probability of lithium dendrite formation during the charge and discharge process. Even at nanometer size, the sulfide electrolyte can still inhibit the formation of lithium dendrites in the positive electrode active material layer during the charge and discharge cycle, effectively reducing the risk of short circuits in the battery charge and discharge cycle, and increasing the cycle life of the battery.
[0036] In some embodiments, in the sulfide electrolyte of the compound of formula I, the X element includes at least Cl, for example, the X element may be Cl, or co-doped Cl and Br, or co-doped Cl and I, or co-doped Cl, Br and I.
[0037] In some embodiments, in the sulfide electrolyte of the compound of formula I, the M element is selected from at least one of Sb, In, and Bi, that is, the M element can be any one of the elements listed above. For example, it can be Sb, In, or Bi. The M element can also be a combination of any two or more of the elements listed above. For example, codoping of Sb and In, or codoping of Sb and Bi, or codoping of In and Bi, or codoping of Sb, In, and Bi. Among them, the doping elements Sb, Bi, and In are combined with O to form strong M-S bonds and P-O bonds in the sulfide electrolyte, which effectively enhances the structural stability of the sulfide electrolyte, inhibits the reaction of the sulfide electrolyte with water, and improves its antioxidant and hydrolysis resistance in an air environment. At the same time, the doping elements Sb, Bi, and In replacing P in the sulfide electrolyte can increase the lattice distortion of the ionic conductor, broaden the lithium-ion transport channels, lower the activation energy of lithium ions, and improve the ionic conductivity of the sulfide electrolyte. Optionally, the M element at least includes Sb. In addition to the above improvement effects on the sulfide electrolyte, the doping element Sb can also form a Li-Sb alloy layer on the surface of the sulfide electrolyte, and the Li-Sb alloy layer can effectively hinder the growth of lithium dendrites during cycling.
[0038] In some embodiments, in the sulfide electrolyte of the compound of formula I, the doping amount b of the M element satisfies 0 < b ≤ 0.1. For example, the doping amount b of the M element can be 0.01, 0.02, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, or 0.1. Optionally, when the M element is a +5 valence element, the doping amount b of the M element can be 0.04; when the M element is a +3 valence element, the doping amount b of the M element can be 0.02.
[0039] In some embodiments, in the sulfide electrolyte of the compound of formula II, the Q element at least includes Cl. For example, the Q element can be Cl, or codoping of Cl and Br, or codoping of Cl and I, or codoping of Cl, Br, and I.
[0040] In some embodiments, in the sulfide electrolyte of the compound of formula II, the E element includes at least Mg or Ca, for example, the E element can be Mg or Ca, or it can be co-doped with Mg and Ca, or co-doped with Mg and Ba, or co-doped with Mg and Sn, or co-doped with Mg and Zn, or co-doped with Ca and Ba, or co-doped with Ca and Sn, or co-doped with Ca and Zn, or co-doped with Mg, Ca and Cr. Among them, the doping elements Mg and Ca are matched with O to form strong ES bonds and PO bonds in the sulfide electrolyte, which effectively enhances the structural stability of the sulfide electrolyte, inhibits the reaction of the sulfide electrolyte with water, and improves its antioxidant and hydrolysis ability in the air environment; at the same time, the doping elements Mg and Ca replace P in the sulfide electrolyte to increase the lattice distortion of the ion conductor, broaden the transmission channel of lithium ions, reduce the activation energy of lithium ions, and improve the ionic conductivity of the sulfide electrolyte.
[0041] In some embodiments, in the sulfide electrolyte of the compound of formula II, the doping amount g of the E element satisfies 0.01≤g≤0.1, for example, the doping amount g of the E element may be 0.01, 0.02, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09 or 0.1. Optionally, the doping amount g of the E element may be 0.02.
[0042] In some embodiments, the positive electrode active material layer includes a positive electrode active material, and the mass content of the positive electrode active material in the positive electrode active material layer is 50% to 97%, for example, it can be 50%, 60%, 70%, 80%, 90%, 95% or 97%; the mass content of the sulfide electrolyte in the positive electrode active material layer is 1% to 50%, for example, it can be 1%, 3%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%. Based on the nano-characteristics of the sulfide electrolyte, the positive electrode active material layer can still achieve a good ion transmission effect when a small amount of sulfide electrolyte is added, which removes the restriction of the solid-state battery on the minimum amount of solid electrolyte in the positive electrode active material layer, thereby effectively increasing the proportion of positive electrode active materials in the positive electrode sheet and improving the energy density of the solid-state battery.
[0043] In some embodiments, the positive electrode active material layer includes a positive electrode active material, a sulfide electrolyte, a positive electrode binder, a positive electrode conductor and a dispersant, and the mass ratio of the positive electrode active material, the sulfide electrolyte, the positive electrode binder and the positive electrode conductor can be (50-97): (1-50): (0-3): (1-3): (0.01-0.5). Among them, the positive electrode active material is selected from one or more combinations of lithium cobalt oxide (LCO), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium nickel cobalt manganese oxide (NCM), lithium nickel cobalt aluminum oxide (NCA), lithium-rich manganese-based oxide (LRMO) and lithium-containing phosphate. The positive electrode binder is, for example, selected from polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinyl pyrrolidone (PVP), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), polyacrylic acid (PAA), polyurethane, polyvinyl alcohol (PVA), sodium alginate (Alg), ethylene-propylene-diene monomer, styrene-butadiene rubber, polyvinylidene fluoride, fluororubber, β-cyclodextrin polymer (β-CDp), polypropylene emulsion (LA132), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymer (ETFE), fluorinated ethylene-propylene copolymer (FEP), perfluoroalkoxy resin (PFA), polychlorotrifluoroethylene (PCTFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-chlorotrifluoroethylene copolymer One or more combinations thereof. The positive electrode conductive agent is, for example, one or a combination of carbon black, Ketjen black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, porous carbon, etc. In one example, the positive electrode conductive agent includes carbon black and carbon nanofibers, and the mass ratio of carbon black to carbon nanofibers is 1:(0.2-1.5).
[0044] In some embodiments, the negative electrode plate can be a metal lithium plate, a metal indium plate, or a lithium-containing alloy plate (such as a lithium-tin-indium alloy plate, a lithium-silicon alloy plate, a lithium-tin alloy plate, or a lithium-aluminum alloy plate). For example, in one example, the negative electrode plate is selected from a metal lithium plate.
[0045] In other embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer coated on at least one side of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material, a sulfide electrolyte, a negative electrode binder, and a negative electrode conductive agent. The mass ratio of the negative electrode active material, the solid electrolyte, the negative electrode binder, and the negative electrode conductive agent can be (50-97): (1-50): (0-3): (1-10). Among them, the negative electrode active material is selected from one or more of tin, artificial graphite (single crystal graphite, polycrystalline graphite, pyrolytic graphite, graphite fiber, etc.), natural graphite (block graphite, flake graphite, earthy graphite, etc.), soft carbon, hard carbon, pure silicon (crystalline silicon, amorphous silicon or organic silicon), silicon oxide compounds, silicon carbon compounds, and nano metal oxides (Fe2O3, CuO, SnO2, Mn3O4 nanoparticles). The negative electrode binder is selected from polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinyl pyrrolidone (PVP), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), polyacrylic acid (PAA), polyurethane, polyvinyl alcohol (PVA), sodium alginate (Alg), ethylene-propylene-diene monomer, styrene-butadiene rubber, polyvinylidene fluoride, fluororubber, β-cyclodextrin polymer (β-CDp), polypropylene emulsion (LA132), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymer (ETFE), fluorinated ethylene-propylene copolymer (FEP), perfluoroalkoxy resin (PFA), polychlorotrifluoroethylene (PCTFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-chlorotrifluoroethylene copolymer One or more combinations thereof. The negative electrode conductive agent is selected from one of graphite, carbon black, acetylene black, graphene, carbon nanotubes, and carbon nanofibers, or a combination of two or more of the two selected in any proportion.
[0046] On the other hand, the present invention also provides a method for preparing a solid-state battery, which comprises: providing a positive electrode sheet, a solid electrolyte membrane and a negative electrode sheet; assembling the positive electrode sheet, the solid electrolyte membrane and the negative electrode sheet into a battery cell, and encapsulating the battery cell to obtain a solid-state battery.
[0047] It should be noted that the negative electrode sheet, solid electrolyte membrane and solid-state battery assembly process in the solid-state battery can be prepared by conventional methods in the art.
[0048] In some embodiments, the negative electrode sheet preparation process is as follows: after mixing the negative electrode material, solid electrolyte, negative electrode binder, and negative electrode conductive agent in a mass ratio of (50-97): (1-50): (0-3): (1-10), deionized water is added to adjust the solid content of the slurry to 55%, and then the negative electrode slurry is fully stirred and mixed under the action of a vacuum mixer to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on an 8μm negative electrode current collector copper foil; after drying at room temperature, it is transferred to an oven for drying, and then cold pressed, cut, and other processes are performed to obtain a negative electrode sheet. Among them, the negative electrode active material is selected from one or more of tin, artificial graphite (single crystal graphite, polycrystalline graphite, pyrolytic graphite, graphite fiber, etc.), natural graphite (block graphite, flake graphite, earthy graphite, etc.), soft carbon, hard carbon, pure silicon (crystalline silicon, amorphous silicon or organic silicon), silicon oxide compounds, silicon carbon compounds, and nano metal oxides (Fe2O3, CuO, SnO2, Mn3O4 nanoparticles). The negative electrode binder is selected from polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinyl pyrrolidone (PVP), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), polyacrylic acid (PAA), polyurethane, polyvinyl alcohol (PVA), sodium alginate (Alg), ethylene-propylene-diene monomer, styrene-butadiene rubber, polyvinylidene fluoride, fluororubber, β-cyclodextrin polymer (β-CDp), polypropylene emulsion (LA132), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymer (ETFE), fluorinated ethylene-propylene copolymer (FEP), perfluoroalkoxy resin (PFA), polychlorotrifluoroethylene (PCTFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-chlorotrifluoroethylene copolymer One or more combinations thereof. The negative electrode conductive agent is selected from one of graphite, carbon black, acetylene black, graphene, carbon nanotubes, and carbon nanofibers, or a combination of two or more of the two selected from the group consisting of graphite, carbon black, acetylene black, graphene, carbon nanotubes, and carbon nanofibers in any proportion.
[0049] In other embodiments, a metal lithium sheet, a metal indium sheet, or a lithium-containing alloy sheet (such as a lithium-tin-indium alloy sheet, a lithium-silicon alloy sheet, a lithium-tin alloy sheet, or a lithium-aluminum alloy sheet) is used as the negative electrode sheet.
[0050] In some embodiments, the solid electrolyte membrane is prepared as follows: a sulfide electrolyte is cold-pressed at a pressure of 300 MPa to 400 MPa to obtain a solid electrolyte membrane.
[0051] The following is an example description of the assembly method of the solid-state battery: integrating the positive electrode sheet on one side of the solid electrolyte membrane, for example, placing the solid electrolyte membrane on the positive electrode active material layer of the positive electrode sheet, and pressing the solid electrolyte membrane and the positive electrode sheet into one at a pressure of 300 MPa; and then integrating the negative electrode sheet on the other side of the solid electrolyte membrane, for example, placing the negative electrode sheet on the other side of the solid electrolyte membrane, so that the negative electrode active material layer of the negative electrode sheet is in contact with the solid electrolyte membrane, and pressing the negative electrode sheet, the solid electrolyte membrane and the positive electrode sheet into one at a pressure of 300 MPa; after sealing and packaging the pressed battery cell under vacuum or inert atmosphere, a solid-state lithium-ion battery can be obtained.
[0052] The solid-state battery assembled with a composite positive electrode with a nano-sulfide electrolyte has increased the number of stable cycles by more than 5 times at a current rate of 1C / 1C.
[0053] like Figure 1 As shown, the method for preparing the positive electrode sheet in the above solid-state battery includes the following steps:
[0054] S1. preparing a sulfide electrolyte;
[0055] S2, adding a positive electrode raw material including a positive electrode active material, a positive electrode conductive agent, the sulfide electrolyte and a dispersant into a solvent to obtain a mixed solution; the solvent includes a protic solvent and an aprotic solvent, and the mass ratio of the protic solvent to the aprotic solvent is 1:(1-10);
[0056] S3, removing the solvent in the mixed solution to obtain a composite positive electrode raw material;
[0057] S4. Mixing a positive electrode binder with the composite positive electrode raw material to prepare a positive electrode coating, and coating the positive electrode coating on a positive electrode current collector to obtain a positive electrode sheet.
[0058] When preparing the positive electrode raw material, the preparation method uses proton & non-proton solvents to dissolve and reprecipitate the mixed sulfide electrolyte in the positive electrode raw material. The dispersant dissolved in the mixed solution will adsorb the sulfide electrolyte molecules during the sulfide electrolyte nucleation and particle formation process to avoid excessive aggregation during the desolvation process, thereby effectively limiting the particle size of the sulfide electrolyte precipitated in the composite positive electrode raw material, and making the nano-sized sulfide electrolyte uniformly attached to the particle surface of the positive electrode active material during precipitation, thereby forming a dense and uniform ion transmission network surrounding the positive electrode active material particles in the subsequently prepared positive electrode active material layer.
[0059] In step S1, the prepared sulfide electrolyte includes Li a P 1-b M b S c O dX e and Li f P 1-g E g S w O y Q z One or more of them, 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + y < 6, 0 < z < 2, M includes at least one of Al, Ga, In, Ti, Sc, As, Sb, Bi, As, V, Nb, X includes at least one of Cl, Br, I, E includes at least one of Mg, Ca, Sr, Ba, Zn, Cr, Sn, Pb, and Q includes at least one of Cl, Br, I.
[0060] In some embodiments, for the preparation method of the sulfide electrolyte Li a P 1-b M b S c O d X e includes the following steps: Under a protective atmosphere, mix a lithium source, a phosphorus source, an M source, a sulfur source, an oxygen source, and an X source according to a preset stoichiometric ratio and place them into a ball milling tank for ball milling treatment; then sinter the ball-milled mixture to obtain the sulfide electrolyte Li a P 1-b M b S c O d X e .
[0061] In some embodiments, for the preparation method of the sulfide electrolyte Li f P 1-g E g S w O y Q z includes: Under a protective atmosphere, mix a lithium source, a phosphorus source, an E source, a sulfur source, an oxygen source, and a Q source according to a preset stoichiometric ratio and place them into a ball milling tank for ball milling treatment, and then sinter the ball-milled mixture to obtain the sulfide electrolyte Li f P 1-g E g S w O y Q z .
[0062] In the above embodiments, the lithium source can be selected from lithium-containing compounds. Further, the lithium source is selected from one or more of LiCl, LiBr, LiI, Li2S. For example, the lithium source is selected from Li2S, or LiCl, or a combination of Li2S and LiCl, etc.
[0063] The phosphorus source is selected from phosphorus-containing compounds. Further, the phosphorus source is selected from one or more of P2S5 and P2O5. Specifically, it can be P2S5, or P2O5, or a combination of P2S5 and P2O5, and the like.
[0064] The sulfur source is selected from sulfur-containing compounds. Further, the sulfur source is selected from at least one of S, Li2S, P2S5, and soft acid metal oxides. Specifically, it can be S, or Li2S, or P2S5, or a combination of Li2S and P2S5, and the like.
[0065] The oxygen source is selected from oxygen-containing compounds. Further, the oxygen source is selected from at least one of Li2O, LiOH, P2O5, and soft acid metal oxides. Specifically, it can be Li2O, LiOH, P2O5, or a combination of Li2O and LiOH, etc.
[0066] The M source is selected from compounds containing the M element. Further, the M source is selected from at least one of halides containing the M element, sulfides containing the M element, and metal oxides containing the M element.
[0067] The E source is selected from compounds containing the E element. Further, the E source is selected from at least one of halides containing the E element, sulfides containing the E element, and metal oxides containing the E element.
[0068] The X source and the Q source are selected from at least one of LiCl, LiBr, and LiI. For example, the X source and the Q source can be LiCl, or LiBr, or LiI, or a combination of LiCl and LiBr, or a combination of LiBr and LiI, or a combination of LiCl, LiBr, and LiI, and the like.
[0069] In some embodiments, the ball milling treatment of the sulfide electrolyte raw material in step S1 can obtain particles with uniform particle size and fine particles. Specifically, after each raw material is mixed evenly according to the stoichiometric ratio, it is added to the ball milling jar for ball milling. During ball milling, the ball-to-material ratio and the amount of solvent added will affect the effect of wet ball milling. The larger the ball-to-material ratio, the higher the grinding efficiency and the finer the material particle size; the selection of the ball-to-material ratio can be determined according to the properties of the raw materials and the process requirements. For harder raw materials, a higher ball-to-material ratio can be selected to improve the grinding effect; and for softer raw materials, a lower ball-to-material ratio can be selected. In one embodiment, the ball-to-material mass ratio in the ball milling jar is (1 to 30): 1, for example, the ball-to-material ratio can be 1: 1, 10: 1, 20: 1 or 30: 1, etc.; the ball milling time is 5 to 20 hours, for example, it can be 5 hours, 10 hours, 15 hours or 20 hours, etc. The ball milling speed is 1 to 1000 rpm, and further the ball milling speed is 100 to 800 rpm, for example, the ball milling speed can be 300 rpm, 500 rpm or 800 rpm, and so on.
[0070] In some embodiments, the sintering temperature of the raw material in step S1 is 200° C. to 600° C., for example, 200° C., 300° C., 400° C., 500° C. or 600° C. The sintering time is 0.1 to 24 hours, and further can be 5 to 20 hours, for example, 5 hours, 10 hours, 15 hours or 20 hours.
[0071] Step S2 specifically includes mixing the positive electrode active material, sulfide electrolyte, and positive electrode conductive agent in the positive electrode raw material in a mass ratio of (50-97): (1-50): (0.05-10) and placing them in a solvent; after the sulfide electrolyte is completely dissolved in the solvent, a dispersant is continued to be added to the solvent to obtain a mixed solution. Among them, the mass ratio of the protic solvent and the aprotic solvent is any value in 1: (1-10), for example, it can be 1: 1, 1: 2, 1: 4, 1: 5, 1: 6, 1: 8 or 1: 10. The protic solvent in the solvent plays a role in dissolving the sulfide electrolyte, and the aprotic solvent plays a role as a surfactant, inducing nano-scale sulfide electrolyte particles to precipitate on the surface of the positive electrode active material. The mass ratio of the protic solvent and the aprotic solvent in the solvent is limited to any value in the appropriate range of 1: (1-10), which can take into account the nano-sizing and uniform precipitation of the sulfide electrolyte in the composite positive electrode raw material. If the proton solvent content is too high (the mass ratio of proton solvent to non-proton solvent is greater than 1:1), the sulfide electrolyte will not be completely precipitated during the precipitation process, thereby affecting the conductive properties of the positive electrode; when the proton solvent content is too low (the mass ratio of proton solvent to non-proton solvent is less than 1:10), the solvent will not be able to fully dissolve the sulfide electrolyte, and some sulfide electrolytes will not be able to be nano-sized.
[0072] In some embodiments, in the mixed solution, the mass ratio of the final precipitated composite positive electrode raw material to the solvent is 1: (1-20), for example, 1: 1, 1: 2, 1: 3, 1: 5, 1: 8, 1: 10, 1: 15 or 1: 20. The composite positive electrode raw material comprises a positive electrode active material, a sulfide electrolyte, a positive electrode conductive agent and a dispersant.
[0073] In some embodiments, the protic solvent includes at least one of ethanol and methanol, and optionally, the protic solvent can be ethanol; the aprotic solvent includes at least one of toluene, xylene, benzene, acetonitrile, ether and carbon tetrachloride, and optionally, the aprotic solvent is selected from at least one of acetonitrile and carbon tetrachloride, for example, the aprotic solvent can be acetonitrile, or carbon tetrachloride, or a mixture of acetonitrile and carbon tetrachloride in any proportion.
[0074] In some embodiments, the dispersant includes at least one of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium sulfonate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium octyl sulfonate, polyethylene glycol octanol ether, polysorbate, polyoxyethylene stearyl alcohol ether, sodium coconut oil, sodium palmitate, sodium olive oil, sodium dodecyl sulfonate and sodium polyacrylate. The mass content of the dispersant in the positive electrode raw material is 0.01% to 0.5%, for example, the mass content of the dispersant can be 0.01%, 0.05%, 0.2%, 0.3%, 0.4% or 0.5%.
[0075] Step S3 specifically includes using a shaker to homogenize the mixed solution, and then placing the homogenized mixed solution in a vacuum environment and heating it, and when the solvent in the mixed solution is completely removed, a reprecipitated composite positive electrode raw material can be obtained, and the average particle size D50 of the sulfide electrolyte in the composite positive electrode raw material satisfies 50nm≤D50<1μm. Among them, the sulfide electrolyte dissolved in the mixed solution cannot aggregate to form large-sized particles due to the action of the dispersant during the reprecipitation process, and then uniformly precipitates in the composite positive electrode raw material as nanosized small-sized particles; at the same time, the sulfide electrolyte is also affected by the aprotic solvent during the precipitation process, and then uniformly adheres to the surface of the positive electrode active material particles activated by the aprotic solvent, and finally forms a dense and uniform ion transport network surrounding the positive electrode active material particles in the subsequently prepared positive electrode active material layer.
[0076] In some embodiments, the vacuum drying temperature for the mixed solution is any value in the range of 25 to 200° C., for example, 25° C., 30° C., 40° C., 50° C., 75° C., 100° C., 120° C., 140° C., 150° C., 180° C., or 200° C. The vacuum drying time for the mixed solution is any value in the range of 0.1 to 24 h, for example, 0.1 h, 0.5 h, 1 h, 2 h, 5 h, 8 h, 10 h, 13 h, 15 h, 20 h, or 24 h.
[0077] In step S4, the composite positive electrode raw material and the positive electrode binder are mixed evenly in a mass ratio of 100:(1-3) to obtain a positive electrode coating, and the positive electrode coating is coated on the positive electrode collector, and the positive electrode sheet is obtained after drying, cold pressing and cutting.
[0078] The technical scheme of the present invention is described in detail below through several specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available products or can be prepared by conventional methods in the art.
[0079] Example 1
[0080] This embodiment provides a positive electrode sheet, and the preparation method of the positive electrode sheet is as follows:
[0081] S1. In an argon atmosphere, 2 mol Li2S, 1.5 mol LiCl, 0.48 mol P2S5, and 0.02 mol Sb2O5 raw materials were added into a ball mill with a ball-to-material ratio of 30:1 and a rotation speed of 500 rpm for 20 h. The precursor powder obtained by ball milling was then sintered at 500 °C for 10 h to obtain the sulfide electrolyte Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 .
[0082] S2, weigh 2g of positive electrode raw material and add it to 10g of solvent. After the sulfide electrolyte in the positive electrode raw material is completely dissolved, polyethylene glycol octanol ether, a dispersant accounting for 0.01% of the mass of the positive electrode raw material, is added to the solvent to obtain a mixed solution; wherein the positive electrode raw material includes 93wt% of the positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2, 5wt% sulfide electrolyte Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 , 2wt% positive electrode conductive agent (super-P and VGCF in a mass ratio of 1:1); the solvent includes a protic solvent ethanol and an aprotic solvent acetonitrile, and the mass ratio of the protic solvent to the aprotic solvent is 1:9.
[0083] S3, homogenizing the mixed solution using a shaker, and then drying the mixed solution in a vacuum oven at 80° C. for 12 h to remove the solvent in the mixed solution, thereby obtaining a composite positive electrode raw material having a nano-sulfide electrolyte;
[0084] S4. The composite positive electrode raw material and the positive electrode adhesive are mixed in a mass ratio of 100:1 to prepare a positive electrode coating, and the positive electrode coating is coated on the positive electrode current collector aluminum foil. After drying, cold pressing and cutting, a positive electrode sheet with a diameter of 10 mm is obtained.
[0085] Example 2
[0086] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 1. The difference between this embodiment and embodiment 1 is that in step S2, a dispersant polyethylene glycol octanol ether is added to the solvent in an amount of 0.05% by weight of the positive electrode raw material.
[0087] Example 3
[0088] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 1. The difference between this embodiment and embodiment 1 is that in step S2, a dispersant polyethylene glycol octanol ether accounting for 0.1% by weight of the positive electrode raw material is added to the solvent.
[0089] Example 4
[0090] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 1. The difference between this embodiment and embodiment 1 is that in step S2, a dispersant polyethylene glycol octanol ether accounting for 0.2% by weight of the positive electrode raw material is added to the solvent.
[0091] Example 5
[0092] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 1. The difference between this embodiment and embodiment 1 is that in step S2, a dispersant polyethylene glycol octanol ether accounting for 0.5% by weight of the positive electrode raw material is added to the solvent.
[0093] Example 6
[0094] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 1. The difference between this embodiment and embodiment 1 is that in step S2, the positive electrode raw material includes 50wt% of the positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2, 48wt% sulfide electrolyte Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 , 2wt% positive electrode conductive agent (super-P and VGCF in a mass ratio of 1:1).
[0095] Example 7
[0096] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 1. The difference between this embodiment and embodiment 1 is that in step S2, the positive electrode raw material includes 70wt% of the positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2, 28wt% sulfide electrolyte Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 , 2wt% positive electrode conductive agent (super-P and VGCF in a mass ratio of 1:1).
[0097] Example 8
[0098] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 1. The difference between this embodiment and embodiment 1 is that in step S2, the positive electrode raw material includes 90wt% of the positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2, 8wt% sulfide electrolyte Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 , 2wt% positive electrode conductive agent (super-P and VGCF in a mass ratio of 1:1).
[0099] Example 9
[0100] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 1. The difference between this embodiment and embodiment 1 is that in step S2, the positive electrode raw material includes 97wt% of the positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2, 1wt% sulfide electrolyte Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 , 2wt% positive electrode conductive agent (super-P and VGCF in a mass ratio of 1:1).
[0101] Example 10
[0102] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S1, the sulfide electrolyte chemical formula prepared by using 2 mol Li2S, 1.5 mol LiCl, 0.495 mol P2S5, and 0.005 mol Sb2O5 raw materials is Li 5.5 P 0.99 Sb 0.01 S 4.475 O 0.025 Cl 1.5 .
[0103] Embodiment 11
[0104] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S1, the sulfide electrolyte chemical formula prepared by using 2 mol Li2S, 1.5 mol LiCl, 0.47 mol P2S5, and 0.03 mol Sb2O5 raw materials is Li 5.5 P 0.94 Sb0.06 S 4.35 O 0.15 Cl 1.5 .
[0105] Example 12
[0106] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S1, the sulfide electrolyte chemical formula prepared by using 2 mol Li2S, 1.5 mol LiCl, 0.45 mol P2S5, and 0.05 mol Sb2O5 raw materials is Li 5.5 P 0.9 Sb 0.1 S 4.25 O 0.25 Cl 1.5 .
[0107] Embodiment 13
[0108] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S1, the sulfide electrolyte chemical formula prepared by using 2 mol Li2S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI, 0.48 mol P2S5, and 0.02 mol Sb2O5 raw materials is Li 5.5 P 0.96 Sb 0.04 S 4.4 O 0.1 Cl 1.3 Br 0.1 I 0.1 .
[0109] Embodiment 14
[0110] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S1, the sulfide electrolyte chemical formula prepared by using 2.4 mol Li2S, 1.1 mol LiCl, 0.48 mol P2S5, and 0.02 mol Sb2O5 raw materials is Li 5.9 P 0.96 Sb 0.04 S 4.8 O 0.10 Cl 1.1
[0111] Embodiment 15
[0112] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S1, the sulfide electrolyte chemical formula prepared by using 1.6 mol Li2S, 1.9 mol LiCl, 0.48 mol P2S5, and 0.02 mol Sb2O5 raw materials is Li 5.1 P 0.96 Sb 0.04 S4O 0.10 Cl 1.9
[0113] Example 16
[0114] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S1, the sulfide electrolyte chemical formula prepared by using 2.01 mol Li2S, 1.5 mol LiCl, 0.495 mol P2S5, and 0.005 mol In2O3 raw materials is Li 5.52 P 0.99 In 0.01 S 4.485 O 0.015 Cl 1.5 .
[0115] Embodiment 17
[0116] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S1, the sulfide electrolyte chemical formula prepared by using 2.02 mol Li2S, 1.5 mol LiCl, 0.49 mol P2S5, and 0.01 mol In2O3 raw materials is Li 5.54 P 0.98 In 0.02 S 4.47 O 0.03 Cl 1.5 .
[0117] Embodiment 18
[0118] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S1, the sulfide electrolyte chemical formula prepared by using 2.06 mol Li2S, 1.5 mol LiCl, 0.47 mol P2S5, and 0.03 mol In2O3 raw materials is Li 5.62 P 0.94 In 0.06 S 4.41 O 0.09 Cl 1.5 .
[0119] Embodiment 19
[0120] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S1, the sulfide electrolyte chemical formula prepared by using 2.1 mol Li2S, 1.5 mol LiCl, 0.45 mol P2S5, and 0.05 mol In2O3 raw materials is Li 5.7 P 0.9 In 0.1 S 4.35 O 0.15 Cl 1.5 .
[0121] Embodiment 20
[0122] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S1, the sulfide electrolyte chemical formula prepared by using 2.02 mol Li2S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI, 0.49 mol P2S5, and 0.01 mol In2O3 raw materials is Li 5.54 P 0.98 In 0.02 S 4.47 O 0.03 Cl 1.3 Br 0. 1I 0.1 .
[0123] Embodiment 21
[0124] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S1, the sulfide electrolyte chemical formula prepared by using 2.01 mol Li2S, 1.5 mol LiCl, 0.495 mol P2S5, and 0.005 mol Bi2O3 raw materials is Li 5.52 P 0.99 Bi 0.01 S 4.485 O 0.015 Cl 1.5 .
[0125] Embodiment 22
[0126] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S1, the sulfide electrolyte chemical formula prepared by using 2.02 mol Li2S, 1.5 mol LiCl, 0.49 mol P2S5, and 0.01 mol Bi2O3 raw materials is Li 5.54 P 0.98 Bi0.02 S 4.47 O 0.03 Cl 1.5 .
[0127] Embodiment 23
[0128] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S1, the sulfide electrolyte chemical formula prepared by using 2.06 mol Li2S, 1.5 mol LiCl, 0.47 mol P2S5, and 0.03 mol Bi2O3 raw materials is Li 5.62 P 0.94 Bi 0.06 S 4.41 O 0.09 Cl 1.5 .
[0129] Embodiment 24
[0130] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S1, the sulfide electrolyte chemical formula prepared by using 2.1 mol Li2S, 1.5 mol LiCl, 0.45 mol P2S5, and 0.05 mol Bi2O3 raw materials is Li 5.7 P 0.9 Bi 0.1 S 4.35 O 0.15 Cl 1.5 .
[0131] Embodiment 25
[0132] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S1, the sulfide electrolyte chemical formula prepared by using 2.02 mol Li2S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI 0.49 mol P2S5, and 0.01 mol Bi2O3 raw materials is Li 5.54 P 0.98 Bi 0.02 S 4.47 O 0.03 Cl 1.3 Br 0. 1I 0.1 .
[0133] Embodiment 26
[0134] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S1, the sulfide electrolyte chemical formula prepared by using 2.015 mol Li2S, 1.5 mol LiCl, 0.495 mol P2S5, and 0.01 mol MgO raw materials is Li 5.53 P 0.99 Mg 0.01 S 4.49 O 0.01 Cl 1.5 .
[0135] Embodiment 27
[0136] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S1, the sulfide electrolyte chemical formula prepared by using 2.03 mol Li2S, 1.5 mol LiCl, 0.49 mol P2S5, and 0.02 mol MgO raw materials is Li 5.56 P 0.98 Mg 0.02 S 4.48 O 0.02 Cl 1.5 .
[0137] Embodiment 28
[0138] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S1, the sulfide electrolyte chemical formula prepared by using 2.09 mol Li2S, 1.5 mol LiCl, 0.47 mol P2S5, and 0.06 mol MgO raw materials is Li 5.68 P 0.94 Mg 0.06 S 4.44 O 0.06 Cl 1.5 .
[0139] Embodiment 29
[0140] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S1, the sulfide electrolyte chemical formula prepared by using 2.15 mol Li2S, 1.5 mol LiCl, 0.45 mol P2S5, and 0.1 mol MgO raw materials is Li 5.8 P 0.9 Mg 0.1 S 4.48 O 0.1 Cl 1.5 .
[0141] Embodiment 30
[0142] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S1, the sulfide electrolyte chemical formula prepared by using 2.03 mol Li2S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI, 0.49 mol P2S5, and 0.02 mol MgO raw materials is Li 5.56 P 0.98 Mg 0.02 S 4.48 O 0.02 Cl 1.3 Br 0.1 I0 .1 .
[0143] Embodiment 31
[0144] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S1, the sulfide electrolyte chemical formula prepared by using 3.43 mol Li2S, 0.1 mol LiCl, 0.49 mol P2S5, and 0.02 mol MgO raw materials is Li 6.96 P 0.98 Mg 0.02 S 5.88 O 0.02 Cl 0.1 .
[0145] Embodiment 32
[0146] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S1, the sulfide electrolyte chemical formula prepared by using 1.83 mol Li2S, 1.9 mol LiCl, 0.49 mol P2S5, and 0.02 mol MgO raw materials is Li 5.16 P 0.98 Mg 0.02 S 4.08 O 0.02 Cl 1.9 .
[0147] Embodiment 33
[0148] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S1, the sulfide electrolyte chemical formula prepared by using 2.03 mol Li2S, 1.5 mol LiCl, 0.49 mol P2S5, and 0.02 mol CaO raw materials is Li 5.56 P 0.98 Ca0.02 S 4.48 O 0.02 Cl 1.5 .
[0149] Embodiment 34
[0150] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S2, the solvent used is a mixed solvent including protic solvent methanol and aprotic solvent acetonitrile, and the mass ratio of protic solvent methanol to aprotic solvent acetonitrile is 1:9.
[0151] Embodiment 35
[0152] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S2, the solvent used is a mixed solvent including protic solvent ethanol and aprotic solvent toluene, and the mass ratio of protic solvent ethanol to aprotic solvent toluene is 1:9.
[0153] Embodiment 36
[0154] This embodiment prepares a positive electrode sheet with the same component system as that of embodiment 3. The difference between this embodiment and embodiment 3 is that in step S2, the solvent used includes a mixed solvent of protic solvent ethanol and aprotic solvent carbon tetrachloride, and the mass ratio of protic solvent ethanol to aprotic solvent carbon tetrachloride is 1:9.
[0155] Comparative Example 1
[0156] This comparative example provides a positive electrode sheet with the same component system as Example 3. The difference between this comparative example and Example 3 is that in step S2, the sulfide electrolyte chemical formula prepared by using 2 mol Li2S, 1.5 mol LiCl, and 0.5 mol P2S5 raw materials is Li 5.5 PS 4.5 Cl 1.5 .
[0157] Comparative Example 2
[0158] This comparative example provides a positive electrode sheet with the same component system as Example 3, and the particle size of the sulfide electrolyte in the positive electrode active material layer of the positive electrode sheet of this comparative example is 10 μm. The preparation method of the positive electrode sheet is as follows:
[0159] S1. In an argon atmosphere, 2 mol Li2S, 1.5 mol LiCl, 0.48 mol P2S5, and 0.02 mol Sb2O5 raw materials were added into a ball mill with a ball-to-material ratio of 30:1 and a rotation speed of 500 rpm for 20 h. The precursor powder obtained by ball milling was then sintered at 500 °C for 10 h to obtain the sulfide electrolyte Li 5.5P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 , and screened out the sulfide electrolyte with a particle size of 10 μm as the raw material for preparing the positive electrode;
[0160] S2, the positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2, sulfide electrolyte Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 , positive electrode conductive agent (super-P and VGCF in a mass ratio of 1:1) are mixed in a mass ratio of 93:5:2 to obtain a composite positive electrode raw material; the composite positive electrode raw material and the positive electrode binder PTFE are mixed in a mass ratio of 100:1 to obtain a positive electrode coating; the positive electrode coating is coated on the positive electrode current collector aluminum foil, and after drying, cold pressing and cutting, a positive electrode sheet with a diameter of 10 mm is obtained.
[0161] Comparative Example 3
[0162] This comparative example provides a positive electrode sheet with the same component system as that of comparative example 2. The difference between this comparative example and comparative example 2 is that in step S1, Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 As a raw material for sulfide electrolytes.
[0163] To further verify the efficacy of the present invention, the positive electrode sheets prepared in Examples 1 to 36 and Comparative Examples 1 to 3 were first assembled into solid-state batteries, and the solid-state batteries assembled in Examples 1 to 36 and Comparative Examples 1 to 3 were subjected to cycle performance tests. The positive electrode sheet parameters and the test results of the assembled solid-state batteries are shown in Table 1.
[0164] The solid-state battery preparation process is as follows: weigh 0.2g of sulfide electrolyte powder and place it in a solid-state battery mold, and press it at a pressure of 300MPa for 5 minutes to obtain a solid electrolyte membrane. The solid electrolyte membrane is integrated on the side of the positive electrode plate where the positive electrode active material layer is set, and pressed into one at a pressure of 300Mpa; the lithium metal sheet is used as the negative electrode plate, and the negative electrode plate is integrated on the side of the solid electrolyte plate away from the positive electrode plate, and pressed into one at a pressure of 300Mpa to obtain a battery cell; the battery cell is thermally packaged, and then subjected to static, hot and cold pressing, formation, clamping, capacity division and other processes to obtain a solid-state battery.
[0165] Cycling performance test of solid-state batteries: At room temperature of 25°C, in the test voltage range of 2.5V (discharge cut-off voltage) to 4.3V (charge cut-off voltage), the solid-state battery is charged and discharged in cycles at a charge and discharge current rate of 1C / 1C. When the discharge capacity of the solid-state battery reaches 80% of the first cycle discharge capacity (80% State of Health, 80% SOH), the test stops and the number of cycles at room temperature is recorded.
[0166] Table 1: Preparation parameters of positive electrode sheets of Examples 1 to 36 and Comparative Examples 1 to 3 and cycle performance test results of assembled solid-state batteries
[0167]
[0168]
[0169] Comparing the test results of Examples 1 to 36 and Comparative Example 1, it can be seen that, although the nano-sulfide electrolyte is not doped with relevant metal elements (such as Sb, In, Bi, Mg) in the positive electrode, the solid-state battery equipped with the corresponding positive electrode has almost no cycle performance, and the nano-sulfide electrolyte Li 5.5 PS 4.5 Cl 1.5 Lithium dendrites are easily formed during charging and discharging, causing the solid-state battery to short-circuit soon after cycling.
[0170] By comparing the test results of Examples 1 to 9, Examples 33 to 34, and Comparative Examples 2 to 3, it can be seen that the sulfide electrolyte in the positive electrode plate can be nanosized through the action of proton / aproton solvents and dispersants, so that when a small amount of sulfide electrolyte is added to the positive electrode plate, the normal charge and discharge cycle of the solid-state battery can still be guaranteed, thereby eliminating the restriction on energy density caused by excessive solid electrolyte usage in the positive electrode plate, and ensuring both the capacity and cycle performance of the solid-state battery. In contrast, in Comparative Examples 2 and 3, adding a low dose of large-particle sulfide electrolyte to the positive electrode plate cannot guarantee the normal charge and discharge cycle of the solid-state battery, and the capacity of the solid-state battery will be greatly attenuated after about 50 cycles.
[0171] Comparing the test results of Examples 1 to 5, it can be seen that in the preparation process of the positive electrode sheet, as the amount of dispersant added increases, the particle size of the sulfide electrolyte in the positive electrode sheet becomes smaller and smaller, while the cycle performance of the solid-state battery shows a trend of gradually increasing first and then gradually decreasing as the particle size of the sulfide electrolyte decreases. This is because when the particle size of the sulfide electrolyte decreases from close to the micron level to the nanometer level, the specific surface area of the sulfide electrolyte increases, thereby constructing a denser ion transport network in the positive electrode active material layer; but when the particle size of the sulfide electrolyte is too small, the conductivity of the sulfide electrolyte will be severely reduced, thereby affecting the cycle performance of the solid-state battery.
[0172] Comparing the test results of Example 3 and Examples 6 to 9, it can be seen that as the mass proportion of the positive electrode active material in the positive electrode sheet increases, the capacity density of the positive electrode sheet increases accordingly, but the cycle performance of the solid-state battery decreases accordingly. In order to balance the requirements of energy density and cycle performance, Example 3 may be a preferred ratio.
[0173] Comparing the test results of Examples 3, 33, 34 and 35, it can be seen that the positive electrode sheet prepared with a solvent of ethanol: acetonitrile = 1:9 can achieve better cycle performance, mainly because ethanol can be used as a hydrogen bond donor and acceptor, while acetonitrile is mainly used as a hydrogen bond acceptor. This combination can better meet the hydrogen bond requirements of different solutes, improve solubility and reaction efficiency. Other combinations are insufficient in this regard: methanol has too strong hydrogen bond donor ability, while carbon tetrachloride and toluene lack hydrogen bonding. In addition, the boiling points of ethanol and acetonitrile are moderate, and it is easy to volatilize and precipitate samples after dissolution.
[0174] The present invention provides a solid-state battery and a preparation method thereof. The solid-state battery nanosizes a modified sulfide electrolyte doped in a positive electrode active material layer, thereby forming a tightly distributed ion transport network and a stable electrode / electrolyte interface in the positive electrode active material layer, thereby achieving a good conductive cycle of the battery by adding less sulfide electrolyte to the positive electrode active material layer, thereby improving the energy density and cycle life of the battery; at the same time, the nanosized sulfide electrolyte in the positive electrode active material layer has higher structural strength, can avoid cracking and pulverization during the charge and discharge cycle, and further improves the storage and cycle life of the battery.
[0175] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A solid-state battery, characterized in that: It includes a positive electrode plate, the positive electrode plate includes a positive electrode active material layer, and the positive electrode active material layer includes a sulfide electrolyte, and the average particle size D50 of the sulfide electrolyte satisfies 50 nm ≤ D50 < 1 μm; Wherein, the sulfide electrolyte includes Li a P 1-b M b S c O d X e and Li f P 1-g E g S w O y Q z One or more of; In the Li a P 1-b M b S c O d X e wherein 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2, M comprises at least one of Al, Ga, In, Ti, Sc, As, Sb, Bi, As, V, Nb; X comprises at least one of Cl, Br, I; In the Li f P 1-g E g S w O y Q z wherein, 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + y < 6, 0 < z < 2, E includes at least one of Mg, Ca, Sr, Ba, Zn, Cr, Sn, Pb, and Q includes at least one of Cl, Br, I.
2. The solid-state battery according to claim 1, characterized in that: In the sulfide electrolyte, 0 < b ≤ 0.1, and M includes at least one of Sb, In, and Bi; and / or, 0.01 ≤ g ≤ 0.1, and E includes at least Mg or Ca.
3. The solid-state battery according to claim 1 or 2, characterized in that: In the sulfide electrolyte, X includes at least Cl, and Q includes at least Cl.
4. The solid-state battery according to claim 1, characterized in that: The average particle size D50 of the sulfide electrolyte is 50 nm to 500 nm.
5. The solid-state battery according to claim 1, characterized in that: The positive electrode active material layer includes a positive electrode active material, and the mass content of the positive electrode active material in the positive electrode active material layer is 50% to 97%, and the mass content of the sulfide electrolyte in the positive electrode active material layer is 1% to 50%.
6. A method for preparing a solid-state battery according to any one of claims 1 to 5, characterized in that: It includes: Providing a positive electrode plate, a solid electrolyte membrane, and a negative electrode plate; Pressing the positive electrode plate, the solid electrolyte membrane, and the negative electrode plate into an electrode assembly, and encapsulating to obtain a solid-state battery; Wherein, the preparation method of the positive electrode plate includes: Preparing a sulfide electrolyte; Adding a positive electrode raw material containing a positive electrode active material, a positive electrode conductive agent, and the sulfide electrolyte and a dispersant into a solvent to obtain a mixed solution; the solvent includes a proton solvent and a non-proton solvent, and the mass ratio of the proton solvent to the non-proton solvent is 1:(1 to 10); Removing the solvent in the mixed solution to obtain a composite positive electrode raw material; Mixing a positive electrode binder with the composite positive electrode raw material to prepare a positive electrode coating, and coating the positive electrode coating on a positive electrode current collector to obtain a positive electrode plate.
7. The preparation method according to claim 6, characterized in that: In the mixed solution, the mass ratio of the composite positive electrode raw material to the solvent is 1:(1 to 20).
8. The preparation method according to claim 6, characterized in that: The proton solvent includes at least one of ethanol and methanol, and the non-proton solvent includes at least one of toluene, xylene, benzene, acetonitrile, ether, and carbon tetrachloride.
9. The preparation method according to claim 6, characterized in that: The dispersant includes at least one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, cetyltrimethylammonium sulfonate, sodium dodecyl sulfate, sodium dodecylbenzenesulfonate, sodium octylsulfonate, polyoxyethylene octylphenol ether, polysorbate, polyoxyethylene stearyl alcohol ether, sodium cocoate, sodium palmitate, sodium oleate, sodium dodecylsulfonate, and sodium polyacrylate; the mass content of the dispersant relative to the positive electrode raw material is 0.01% to 0.5%.
10. The preparation method according to claim 6, characterized in that: The sulfide electrolyte includes Li a P 1- b M b S c O d X e and Li f P 1-g E g S w O y Q z One or more of In the Li a P 1-b M b S c O d X e wherein 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2, M comprises at least one of Al, Ga, In, Ti, Sc, As, Sb, Bi, As, V, Nb; X comprises at least one of Cl, Br, I; In the Li f P 1-g E g S w O y Q z wherein, 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + y < 6, 0 < z < 2, E comprises at least one of Mg, Ca, Sr, Ba, Zn, Cr, Sn, Pb; Q comprises at least one of Cl, Br, I; Wherein, Li in the sulfide electrolyte a P 1-b M b S c O d X e The preparation method comprises: mixing and sintering a lithium source, a phosphorus source, a M source, a sulfur source, an oxygen source, and an X source according to a preset stoichiometric ratio to obtain Li a P 1-b M b S c O d X e ; And / or The sulfide electrolyte contains Li f P 1-g E g S w O y Q z The preparation method comprises: mixing and sintering a lithium source, a phosphorus source, an E source, a sulfur source, an oxygen source, and a Q source according to a preset stoichiometric ratio to obtain Li f P 1-g E g S w O y Q z .
Citation Information
Patent Citations
Sulfide-based solid-state battery
CN103733414A
Nanoscale sulfide solid electrolyte material and preparation method thereof
CN115133117A
Electrode layer and all-solid-state battery
CN116487521A
Application of ester substance as surface modifier, battery pole piece and preparation method
CN117638268A
Composite positive electrode material layer and preparation method and application thereof
CN118431406A
Cited By
Solid electrolyte refining method based on hydrogen bond self-assembly composite aprotic solvent and application of solid electrolyte refining method
CN119965375A
A method for refining a solid electrolyte based on hydrogen bond self-assembly composite aprotic solvent and its application
CN119965375B
Composite solid electrolyte layer and preparation method and application thereof
CN120413839A